Burnout Syndrome and its Prevention - Schubertová, Valérie (2024)
This bachelor's thesis focuses on burnout syndrome, which is an increasingly prevalent phenomenon in modern workplaces. The theoretical part of the thesis presents a comprehensive overview of burnout syndrome, including its definitions, historical development, and diagnostic methods. Emphasis is placed on analyzing the causes, symptoms, and consequences of burnout for both individuals and organizations. The practical part involves a secondary analysis of existing qualitative and quantitative data, including case studies and results among hospital nurses. The analysis of existing qualitative and quantitative data enabled detailed examination of burnout syndrome from various perspectives. Qualitative data provided deep insights into the personal experiences and perceptions of burnout among hospital nurses, while quantitative data allowed for the statistical evaluation of the prevention and effectiveness of intervention strategies.